(untitled) (Journal of Hama University, 2022)
Vegetable crops in greenhouses are susceptible to infection with large number of plant viruses belonging to Begomovirus especially Tomato yellow leaf curl virus which cause significant economic losses. This study aimed to detect Sicily strain Tomato yellow leaf curl Sardinia virus-Sicily (TYLCSV-Sic) infecting tomato plants Solanum lycopesicum L. in greenhouses in the Syrian coast region. Generic PCR using degenerate primer AV494/AC1048 results showed that 16 of 19 samples were infected with Begomoviruses. Also generic PCR using degenerate primer TycpV369/TycpC1023 revealed that 15 of the 19 samples were infected with Tomato yellow leaf curl virus (TYLCV). While PCR results using specific primer Sa2267/RVC427 confirmed the presence of TYLCSV-Sic in one of the 19 samples, whereas other samples didn’t react with this primer which indicate that it may be new strains of TYLCV, so there is necessity for more microbiological studies to identify all strains of TYLCV in Syria.